Механическое действие камуфлетного взрыва - Бовт А. Н. Анатолий Николаевич; Ловецкий Е. Е. Евгений Евгеньевич; Селяков В. И. Вячеслав Иванович; Сироткин В. К.; Фетисов В. С.; Шурыгин Е. А. (Москва, Недра, 1990)
Авт. указ. на обороте тит. л.